2009
DOI: 10.1038/nn.2351
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of AMPA receptor extrasynaptic insertion by 4.1N, phosphorylation and palmitoylation

Abstract: The insertion of alpha–amino–3–hydroxy–5–methyl–4–isoxazolepropionic acid receptors (AMPARs) into the plasma membrane is a key step in synaptic delivery of AMPARs during the expression of synaptic plasticity. However, the molecular mechanisms regulating AMPAR insertion remain elusive. By directly visualizing individual insertion events of the AMPAR subunit GluR1, we demonstrate that Protein 4.1N is required for activity dependent GluR1 insertion. PKC phosphorylation of GluR1 S816 and S818 residues enhances 4.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

19
392
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 318 publications
(419 citation statements)
references
References 48 publications
19
392
1
1
Order By: Relevance
“…By using a well-established and specific GluA1-MPR competing peptide (Boehm et al, 2006;Lin et al, 2009;Mitsushima et al, 2011), we show that GluA1-MPR has a key role in shortterm and long-term fear memory but not its retrieval. Furthermore, we show that microinjection of a GluA4-MPR protein fragment (Boehm et al, 2006;Correia et al, 2003;Gomes et al, 2007) impairs long-term but not short-term fear memory formation.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…By using a well-established and specific GluA1-MPR competing peptide (Boehm et al, 2006;Lin et al, 2009;Mitsushima et al, 2011), we show that GluA1-MPR has a key role in shortterm and long-term fear memory but not its retrieval. Furthermore, we show that microinjection of a GluA4-MPR protein fragment (Boehm et al, 2006;Correia et al, 2003;Gomes et al, 2007) impairs long-term but not short-term fear memory formation.…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies have shown that GluA1-MPR and GluA4-MPR, but not GluA2-MPR, are needed for AMPAR insertion into synapse and neuronal membrane and for synaptic plasticity (Shi et al, 2001;Correia et al, 2003;Boehm et al, 2006;Gomes et al, 2007;Lin et al, 2009;Mitsushima et al, 2011). However, the role of AMPAR-MPR in LTM formation is not known.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The band 4.1 proteins have also been shown to interact with and regulate the membrane localization of various receptors. For example, 4.1N interacts with D2 and D3 dopamine receptors (Binda et al, 2002) and AMPA receptors (Lin et al, 2009;Shen et al, 2000) and facilitates the cell surface expression of these receptors. Additionally, 4.1G and 4.1B are required for the proper localization and activation of parathyroid hormone receptors (Saito et al, 2005) and NMDA receptors (Hoy et al, 2009), respectively. A homology search identified 16 proteins containing the FERM domain in Caenorhabditis elegans (Van Furden et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…However, more recently it has been realized that such modifications can also alter the activity of the protein more directly, so should be thought of as a cell signaling event, especially as they are reversible and again akin to phosphorylation. A key example of such an event is the increase in surface expression of AMPA receptors on the post-synaptic membranes of neurons during long-term potentiation, the major cellular model for the formation of memories [27]. Other important, and similar, modifications include SUMOylation [28] and ubiquitination [29].…”
mentioning
confidence: 99%